13=5x+1-3x

Simple and best practice solution for 13=5x+1-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13=5x+1-3x equation:


Simplifying
13 = 5x + 1 + -3x

Reorder the terms:
13 = 1 + 5x + -3x

Combine like terms: 5x + -3x = 2x
13 = 1 + 2x

Solving
13 = 1 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
13 + -2x = 1 + 2x + -2x

Combine like terms: 2x + -2x = 0
13 + -2x = 1 + 0
13 + -2x = 1

Add '-13' to each side of the equation.
13 + -13 + -2x = 1 + -13

Combine like terms: 13 + -13 = 0
0 + -2x = 1 + -13
-2x = 1 + -13

Combine like terms: 1 + -13 = -12
-2x = -12

Divide each side by '-2'.
x = 6

Simplifying
x = 6

See similar equations:

| .20*5000= | | 2975+X(175.75)=5962.72 | | 9+-5x=12+-1(6x+7) | | 0.3(4x-2)=-0.8x+9.4 | | 2c^2+9c+10=0 | | 6000-1240= | | (X+41)+95=x+78 | | 2x+9-x=9+2x-6 | | 74=8(c+4)-4 | | 4760/45= | | 2.5=3.7-0.4x | | 3log(x)=11 | | 5+4x=6x+5-2x | | 8x-1+9x=7x+3-9x | | 2v-13=11 | | f(x)=2x^2+9x-5 | | x=y-0.8 | | 2.6x-1.8y=5.5x-0.8y | | 5x/8-8=x/14+13 | | 5x+9=6(x+2) | | 4y-5=20y+11 | | 3n+yr=r-8h | | -6(3m-5)=-78 | | 2y+4=-6y+10+4y | | x^2+y^2-16*(-2)+8*(-3)-10=0 | | 9(s+8)-23=76 | | 2y+4=8y | | (5x-4+2x^2)(3+4x)= | | 3=-4(4-6p)-(p+4) | | 96=6(v-83)+6 | | y=-32.36x+98.25 | | -5x+29=10x-1 |

Equations solver categories